Plasma-assisted molecular beam epitaxy growth of high-density nitrogen-doped Ga2O3 thin films on Ga2O3 (010) substrates by simultaneously supplying oxygen and nitrogen radicals - Kura Nakaoka; Shoki Taniguchi; Tomoki Uehara; Jin Inajima; Kohki Tsujimoto; Yusuke Teramura; Satoko Honda; YongGu Shim; Masataka Higashiwaki (APL Materials)
We demonstrated plasma-assisted molecular beam epitaxy (MBE) growth of high-density nitrogen (N)-doped Ga2O3 thin films on Ga2O3 (010) substrates by simultaneously supplying oxygen and N radicals. The N density was controlled in a wide range of 1017–1021 cm−3, and single-crystal Ga2O3 thin films with N densities up to 2.9 × 1021 cm−3 were successfully grown. Reflection high-energy electron diffraction images of all MBE-grown N-doped Ga2O3 thin films showed streak patterns, and surface root mean square roughnesses were less than 1.2 nm, indicating that high-quality films were obtained irrespective of the N doping density. Spectroscopic ellipsometry revealed that a N-doped Ga2O3 thin film with N = 2.9 × 1021 cm−3 had a larger refractive index than that of the Ga2O3 film with N = 2.4 × 1018 cm−3, which was probably due to the compositional-level N incorporation of about 4% in the Ga2O3 crystal. The MBE growth technique that enables precise control of the N doping density over five orders of magnitude without compromising crystal quality should be of great help in the future development of various Ga2O3 devices.